The new opt-out Dutch National Breast Implant Registry – Lessons learnt from the road to implementation. Issue 10 (October 2017) - Rakhorst, Hinne A.; Mureau, Marc A.M.; Cooter, Rodney D.; McNeil, John; van Hooff, Miranda; van der Hulst, René; Hommes, Juliette; Hoornweg, Marije; Moojen-Zaal, Laura; Liem, Patricia; Mathijssen, Irene M.J.
Summary: An estimated 1–3% of all women in the Netherlands carry breast implants. Since the introduction five decades ago, problems with a variety of breast implants have emerged with direct consequences for the patients' health. Plastic surgeons worldwide reacted through campaigning for auditing on long-term implant quality, surgeon performance, and institutional outcomes in implant registries. Especially, the PIP implant scandal of 2010 demonstrated the paucity of epidemiological data and uncovered a weakness in our ability to even 'track and trace' patients. In addition, a recent report of the Dutch Institute of National Health showed a lack of compliance of 100% of breast implant producers to CE requirements. These arguments stress the need for an independent implant registry. Insufficient capture rates or dependence from the implant producers made the variety of national and international patient registries unreliable. The Dutch Breast Implant Registry (DBIR) is unique because it is an opt-out registry without the need for informed consent and thus a high capture rate. Furthermore, an estimated 95% of breast implants are implanted by board-certified plastic surgeons. Funding was received from a non-governmental organisation to increase the quality of health care in the Netherlands, and maintenance is gathered by 25 euros per implant inserted. This article describes the way the Dutch have set up their system, with special attention to the well-known hurdles of starting a patient registry. Examples include: funding, medical ethical issues, opt out system, benchmarking, quality assurance as well as governance and collaboration. The Dutch consider their experience and data shareware for others to be used globally to the benefit of patient safety and quality improvement.